How to succeed in exams & assessments - McMillan, Kathleen; Weyers, Jonathan D. B. (Harlow, Essex, England : Prentice Hall, 2009)
How to pass exams & assessment provides everything a student is likely to need to prepare for and perform well in all types of university assessment and examination.
1. Intrduction -- 2. What markers are looking for -- 3. Physical and mental preparation -- 4. Study styles -- 5. Time management -- 6. Revision strategies -- 7. Stress management -- 8. As the exam approaches -- 9. Tackling specific types of exam and assessment
Originally published: Harlow: Pearson Prentice Hall, 2007
Includes bibliographical references
Keywords: Examinations -- Study guides